Multifactorial effects of warming, low irradiance, and low salinity on Arctic kelps - A. Lebrun; C. A. Miller; C. A. Miller; M. Meynadier; S. Comeau; P. Urrutti; S. Alliouane; R. Schlegel; J.-P. Gattuso; J.-P. Gattuso; F. Gazeau (Biogeosciences, 2024)
The Arctic is projected to warm by 2 to 5 °C by the end of the century. Warming causes melting of glaciers, shrinking of the areas covered by sea ice, and increased terrestrial runoff from snowfields and permafrost thawing. Warming, decreasing coastal underwater irradiance, and lower salinity are potentially threatening polar marine organisms, including kelps, that are key species of hard-bottom shallow communities. The present study investigates the physiological responses of four kelp species (Alaria esculenta, Laminaria digitata, Saccharina latissima, and Hedophyllum nigripes) to these environmental changes through a perturbation experiment in ex situ mesocosms. Kelps were exposed for 6 weeks to four experimental treatments: an unmanipulated control; a warming condition under the CO2 emission scenario SSP5-8.5; and two multifactorial conditions combining warming, low salinity, and low irradiance reproducing the future coastal Arctic exposed to terrestrial runoff under two CO2 emission scenarios (SSP2-4.5 and SSP5-8.5). The physiological effects on A. esculenta, L. digitata, and S. latissima were investigated, and gene expression patterns of S. latissima and H. nigripes were analyzed. Across all species and experimental treatments, growth rates were similar, underlying the acclimation potential of these species to future Arctic conditions. Specimens of A. esculenta increased their chlorophyll a content when exposed to low irradiance conditions, suggesting that they may be resilient to an increase in glacier and river runoff with the potential to become more dominant at greater depths. S. latissima showed a lower carbon : nitrogen (C : N) ratio under the SSP5-8.5 multifactorial conditions' treatment, suggesting tolerance to coastal erosion and permafrost thawing. In contrast, L. digitata showed no response to the conditions tested on any of the investigated physiological parameters. The down-regulation of genes coding for heat-shock proteins in H. nigripes and S. latissima underscores their ability to acclimate to heat stress, which portrays temperature as a key influencing factor. Based on these results, it is expected that kelp communities will undergo changes in species composition that will vary at local scale as a function of the changes in environmental drivers.